2016
DOI: 10.1111/maps.12622
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray computed tomography imaging: A not‐so‐nondestructive technique

Abstract: X‐ray computed tomography has become a popular means for examining the interiors of meteorites and has been advocated for routine curation and for the examination of samples returned by missions. Here, we report the results of a blind test that indicate that CT imaging deposits a considerable radiation dose in a meteorite and seriously compromises its natural radiation record. Ten vials of the Bruderheim L6 chondrite were placed in CT imager and exposed to radiation levels typical for meteorite studies. Half w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…As suggested by Uesegi et al (2013), X‐CT will be an important source of information for the analysis of valuable samples collected by future sample return missions. X‐CT causes no major damage on the mineral components, but some studies have suggested that X‐CT can compromise the natural radiation records of the samples (see e.g., Sears et al 2016; Hanna and Ketcham 2018). Friedrich et al (2019) have noticed no variation of the organic component after X‐CT irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Uesegi et al (2013), X‐CT will be an important source of information for the analysis of valuable samples collected by future sample return missions. X‐CT causes no major damage on the mineral components, but some studies have suggested that X‐CT can compromise the natural radiation records of the samples (see e.g., Sears et al 2016; Hanna and Ketcham 2018). Friedrich et al (2019) have noticed no variation of the organic component after X‐CT irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Being totally nondestructive, FTIR microtomography and its characterization of the organics could be the first step of analyses. Some studies suggested that X-CT can cause some damage to the organics (see e.g., Sears et al 2016;Hanna and Ketcham 2017); however, this strongly depends on the experimental conditions used (namely energy and photon density). In any case, in future studies, it will be important to perform FTIR microtomography before X-CT to be able to address this issue.…”
Section: Advantages and Limitations Of Ft-ir Microtomographymentioning
confidence: 99%
“…For example, Sears et al. () and Sears et al. () found that the thermoluminescence (TL) intensity of the Bruderheim L chondrite is substantially altered by exposure to the ionizing radiation of μCT imaging experiments.…”
Section: Introductionmentioning
confidence: 99%